Effects of hydrogen pressure and prior austenite grain size on the hydrogen embrittlement characteristics of a press-hardened martensitic steel. (9th July 2021) - Cho, L.; Bradley, P.E.; Lauria, D.S.; Connolly, M.J.; Seo, E.J.; Findley, K.O.; Speer, J.G.; Golem, L.; Slifka, A.J.
Abstract: The effects of hydrogen gas pressure and prior austenite grain size (PAGS) on the susceptibility of a 22MnB5 press-hardened martensitic steel (PHS) to hydrogen embrittlement were studied. The hydrogen test apparatus at NIST-Boulder was modified for tensile testing of plate-type and sheet-type specimens in gaseous hydrogen. This modification made it possible to evaluate the slow strain rate tensile (SSRT) properties of the PHS with three different PAGS at various hydrogen pressures (0.21 MPa–5.5 MPa). SSRT testing in gaseous hydrogen resulted in significant reductions of both the tensile strength and ductility, as compared to those measured in air. In addition, the presence of gaseous hydrogen resulted in a transition in fracture morphology from the near-45° slant fracture to a more brittle fracture along a plane perpendicular to the tensile axis. The hydrogen-affected fracture zones were connected to the sheet specimen free surfaces, signifying the effect of external hydrogen. The fracture surfaces of the hydrogen-embrittled specimens contained relatively flat, "cleavage-like" facets, the size of which depended on the PAGS or packet size. The PHS having the largest PAGS represented generally larger secondary cracks and straighter crack paths in addition to a greater area fraction of the "cleavage-like" facets, likely indicative of a lower frequency of crack deflections. Compared to the largest PAGS condition, the two PHS with smaller PAGS were more resistant to the hydrogen-induced fracture especially at relatively low hydrogen gas pressures (<0.52 MPa). In contrast, with an increase in hydrogen pressure, all PHS specimens exhibited significant decreases in tensile strength and ductility. The positive effect of refining martensitic microstructure, at the low hydrogen pressures, is likely associated with improved toughness of the smaller grain-sized specimens. Highlights: Gaseous H embrittlement (HE) in ultra-high strength martensitic steel is studied. Test apparatus for sheet-type specimen testing in gaseous H is developed. Martensitic constituent sizes affect HE susceptibility and fracture morphologies. Martensite with smaller prior austenite grain size is more resistant to gaseous HE. Various metallurgical factors related to martensite HE sensitivity are discussed.